Brain Imaging Using Mobile CT: Current Status and Future Prospects. Issue 1 (23rd November 2015) - John, Seby; Stock, Sarah; Cerejo, Russell; Uchino, Ken; Winners, Stacey; Russman, Andrew; Masaryk, Thomas; Rasmussen, Peter; Hussain, Muhammad S.
ABSTRACT: Computed tomography (CT) is an invaluable tool in the diagnosis of many clinical conditions. Several advancements in biomedical engineering have achieved increase in speed, improvements in low‐contrast detectability and image quality, and lower radiation. Portable or mobile CT constituted one such important advancement. It is especially useful in evaluating critically ill, intensive care unit patients by scanning them at bedside. A paradigm shift in utilization of mobile CT was its installation in ambulances for the management of acute stroke. Given the time sensitive nature of acute ischemic stroke, Mobile stroke units (MSU) were developed in Germany consisting of an ambulance equipped with a CT scanner, point of care laboratory system, along with teleradiological support. In a radical reconfiguration of stroke care, the MSU would bring the CT scanner to the stroke patient, without waiting for the patient at the emergency room. Two separate MSU projects in Saarland and Berlin demonstrated the safety and feasibility of this concept for prehospital stroke care, showing increased rate of intravenous thrombolysis and significant reduction in time to treatment compared to conventional care. MSU also improved the triage of patients to appropriate and specialized hospitals. Although multiple issues remain yet unanswered with the MSU concept including clinical outcome and cost‐effectiveness, the MSU venture is visionary and enables delivery of life‐saving and enhancing treatment for ischemic and hemorrhagic stroke. In this review, we discuss the development of mobile CT and its applications, with specific focus on its use in MSUs along with our institution's MSU experience.